Effect of different yolk treatments on cold resistance of boar semen - Martyniuk, Irina; Akimov, Оleksandrv; Paliy, Anatoliy; Pavlichenko, Оlena (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):247